From Haute Cuisine to Ox Roasts: Public Feasting and the Negotiation of Class in Mid-19th-Century Saint John and Halifax - Huskins, Bonnie (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
The primary objective of this paper is to delineate a typology or hierarchy of public feasts in mid 19th-century Saint John and Halifax in order to show how we can use food and drink as markers of class and as instruments in the process of class formation. I will be considering such questions as: why did people in different classes partake of "victuals" and "spirits?"? How does this reflect their different priorities and social practices at mid century? Emphasis will be placed on public secular feasts— that is, the banquet, ox roast, institutional repast, and tea and coffee soirée — which were held to commemorate royal and patriotic anniversaries. It is only through these local micro-studies that we can effectively "get at" the meanings associated with food and drink.